What Is Moral Relativism?. (27th February 2018) - Wreen, Michael
Abstract: The main aim of this paper is to advance, clarify, and defend a definition of relativism. On the definition, relativism does not contrast with absolutism, is not the same as pluralism, contrasts with universalism and nihilism, and is compatible with both moral objectivity and moral subjectivity. Advantages of the definition are noted, but the bulk of the paper is devoted to detailed discussions of the concepts that figure in the definition or are entailed by it. Such concepts include those of a moral code, of conflict between moral codes, and of a convention.